Analysis of the pro-and anti-inflammatory signalling in the aged hippocampus : effect of dexamethasone and vitamin D3 - Moore, Michelle E. (Trinity College (Dublin, Ireland). Department of Physiology, 2006)
The objectives of this study were to establish the cellular events and alterations in signalling associated with ageing and to determine the effectiveness of two anti¬inflammatory agents, dexamethasone and vitamin D3 in attenuating the age-related changes in the hippocampus. The findings of this study report an increase in interleukin (IL)-1β concentration and as it is postulated that a balance exists between the pro- and anti-inflammatory signalling in the brain, a concurrent decrease in IL-10 concentration was also observed in the aged hippocampus. As a consequence, it is not surprising that the activity of downstream IL-1β signalling mediators, namely c-Jun N-terminal kinase (JNK) and caspase-3, were upregulated, while IL-10 signalling, as evidenced by the phosphorylation of Janus kinase1 (JAK1) and signal transducers and activators of transcription-3 (STAT-3), was diminished. The data presented indicate cell deterioration in the aged rat hippocampus as suggested by the increased cleavage of poly (ADP-ribose) polymerase, and this concurs with the impairment in long-term potentiation (LTP) associated with age. This thesis investigated whether the effects of treatment with dexamethasone and vitamin D3 in the periphery were mimicked in the aged hippocampus. These data report abrogation of the age-related imbalance in inflammatory signalling in the hippocampus following treatment with dexamethasone and vitamin D3.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin